Analysis of Service Quality and Tourism Destination Parts on Visitor Satisfaction at Taman Mini Indonesia Indah - Astuti, Nabila Sri; Dewi, Liliana (Jurnal Penelitian Pariwisata, 2022)
This study aims to determine the effect of service quality and part of tourist destinations on visitor satisfaction at Taman Mini Indonesia Indah. The type of research is descriptive quantitative with multiple regression analysis methods. Collecting data by distributing questionnaires with a google form, a sampling technique using accidental sampling. The population in this study were tourists who had visited Taman Mini Indonesia Indah in the last five years, as many as 4,471,504 people. While the sample uses the Slovin formula, the results show a selection of 100 respondents. The results showed that the quality of service and the part of tourist destinations partially and simultaneously affect visitors' satisfaction with Taman Mini Indonesia Indah. The better the quality of service and the 4A tourism components provided by the manager of Taman Mini Indonesia Indah to visitors will increase visitor satisfaction. The manager of Taman Mini Indonesia Indah is expected to provide training to employees so that they can continue to serve well, quickly, responsively, politely, and friendly. The manager of Taman Mini Indonesia Indah is expected to add artificial attractions that can attract tourists. visits from outside Jakarta. Keywords: Service Quality, Destination Part, Visitor Satisfaction